MEASUREMENT OF REFRACTIVE INDEX OF WATER IN COASTAL AREA USING He-Ne LASER AND HOLLOW PRISM - Arlin Maya Sari; Ucia Mahya Dewi; Tulus Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
water samples used were taken from three coastal areas of Aceh, namely Tibang, Uleelheue, and Kaju. Water is taken from 3 different water sources for each area of ​​the region. Initial measurements were made for distilled water to see the accuracy of using a hollow prism made of commercial glass. The water sample is inserted into a hollow prism made of commercial glass with an angle of 450. The helium-neon laser beam with a wavelength of 564 nm is directed to the hollow prism so that it undergoes refraction. The measurement results on the distilled water sample obtained a refractive index of 1.33, the result is the same as the measurement using the Abbe refractometer. Meanwhile, the measurement results found that the refractive index of water taken from water sources in the coastal area has a relatively similar index of refraction. The refractive index of water taken from three coastal areas ranged from 1.341 to 1.349. The value of the refractive index of water is also affected by the level of mineral content and the level of saltiness